The number of grains in a rice panicle as a selection criterion on productivity - P. I. Kostylev; S. S. Popov (Аграрная наука Евро-Северо-Востока, 2016)
Rice yield depends on the number of panicles per area unit, number of grain in a panicle and kernel weight, which are controlled by a quantitative trait locus. Therefore, the selection of plants with more grains in panicle can help to develop more productive varieties. The purpose of the research is the study of the effect of selection on the number of grains in panicle F2 on the productivity of generations F3, and F4. F2-F4 hybrids of crossing between varieties Kuboyar and sample Il. 14 served as a studied material. The experiment was carried out in 2012-2014 in FSUE "Proletarskoe" in Rostov region. Selection of single plants was conducted in F2 populations by number of grain per panicle. From each of three groups 14 recombined plants were selected having low number (M, 27-36 grains), medium number (C, 90-110 grans), and high number (K, 178-239 grains) of grain per panicle for producing F3 generation. Grain yield of F3 families, obtained from selected plants in F2 population based on differences in the number of grains of panicle varied considerably: in the group K on average, 596 g/m2, in group C - 468 g/m2, the group M - 328 g/m2, i.e. at 138-140 g/m2. Grain yield in F3 has moderate correlation with the number of grains per panicle in F2. Correlation of between yields of generations F3 and F4 was also moderate positive and amounted to 0.43 ± 0.12, and the regression is y = 2.87 + 0.68x. This means that at increase in grain yield F3 by 1 t/ha yield in F4 rises an average by 0.68 t/ha. Therefore, the selection of grain number per panicle in the early generations may be appropriate.